2023
DOI: 10.7554/elife.80387
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RNA:protein interactions with an integrative approach leads to the identification of potent YBX1 inhibitors

Abstract: RNA-protein interactions (RPIs) are promising targets for developing new molecules of therapeutic interest. Nevertheless, challenges arise from the lack of methods and feedback between computational and experimental techniques during the drug discovery process. Here, we tackle these challenges by developing a drug screening approach that integrates chemical, structural and cellular data from both advanced computational techniques and a method to score RPIs in cells for the development of small RPI inhibitors; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Brent W. Sutherland identified that activated Akt binds to and phosphorylates the cold shock domain of YB-1 at Ser102, noting that disruption of this phosphorylation site can suppress tumor cell growth [41] . Chen Liang demonstrated that YBX1 modulates the expression of phosphorylated EGFR and AKT, affecting cell apoptosis, cell cycle progression, and invasion without changing the total levels of these proteins [42] . Furthermore, Y. Zhan's research on nasopharyngeal carcinoma showed that YB1 knockdown alters the Akt/mTOR signaling pathway, enhancing cell growth, migration, and invasion [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brent W. Sutherland identified that activated Akt binds to and phosphorylates the cold shock domain of YB-1 at Ser102, noting that disruption of this phosphorylation site can suppress tumor cell growth [41] . Chen Liang demonstrated that YBX1 modulates the expression of phosphorylated EGFR and AKT, affecting cell apoptosis, cell cycle progression, and invasion without changing the total levels of these proteins [42] . Furthermore, Y. Zhan's research on nasopharyngeal carcinoma showed that YB1 knockdown alters the Akt/mTOR signaling pathway, enhancing cell growth, migration, and invasion [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a small molecule derived from azopodophyllotoxin, SU056, exhibits strong inhibition of tumor growth and progression by targeting YB-1 in ovarian cancer (OC). Additionally, the FDA-approved PARP-1 inhibitor, Niraparib, has been shown to attach to YB-1(CSD), disrupting the interactions between RNA and YB-1, and thereby affecting YB-1 mediated cellular functions [42] . Our findings further support that applying targeted strategies against YBX-1, using tools like YBX1 shRNA or specific pharmacological inhibitors, could represent promising strategies for liver cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining the structure of RNA: protein complexes from NMR spectra is more tedious than analyzing X-ray data, but it is feasible. However, the main advantage of NMR spectroscopy for drug discovery is its ability to work in liquid to capture dynamic interactions between small molecules, RNA, and protein residues even with low-affinity compounds ( El Hage et al, 2023 ). Many RBPs targeted by small compounds have been analyzed by NMR [e.g., YBX1 cold-shock domain ( El Hage et al, 2023 ), SPF45 UHM domain ( Jagtap et al, 2020 ), U2AF65 ( Kobayashi et al, 2022 ), Lin28 ( Wang et al, 2018 ), HuR ( Lal et al, 2017 ; Manzoni et al, 2018 ; Wu et al, 2023 ), Musashi ( Lan et al, 2015 ), TDP-43 ( François-Moutal et al, 2019 ; Nshogoza et al, 2019 ), IGF2BP1 ( Dahlem et al, 2022 ; Wallis et al, 2022 )].…”
Section: Structural Data To Validate or Screen Small Molecules Target...mentioning
confidence: 99%
“…The selection of small molecules requires high-throughput screening using various techniques ( Julio and Backus, 2021 ), including fluorescence polarization or FRET (fluorescence resonance energy transfer), for which advantages and disadvantages are discussed. While in vitro approaches are valuable, it is also important to determine whether small molecules are on-target in a cellular context ( El Hage et al, 2023 ). Several parameters, such as membrane crossing, specific folding within cells, and non-specific binding to other biomolecules, cannot be predicted in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…RNA–protein interactions, controlling all aspects of RNA metabolism such as splicing, export, localization, stability, and translation, majorly contribute to the cell's response to stress (Harvey et al, 2017). Therefore, on one hand, dysfunction of RNA–protein interactions leads to pathological responses and disease, whereas on the other RNA–protein interactions are emergent therapeutic targets (El Hage et al, 2023; Gebauer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%